The diagnosis and management of subclinical hypothyroidism is assay‐dependent– Implications for clinical practice. (4th February 2021) - Kalaria, Tejas; Sanders, Anna; Fenn, Jonathan; Ashby, Helen L.; Mohammed, Pervaz; Buch, Harit N.; Ford, Clare; Gama, Rousseau
Abstract: Objective: We assessed the commutativity of Roche and Abbott thyroid assays in the diagnosis and management of subclinical hypothyroidism (SCH). The Roche and Abbott thyroid assays are used by approximately 75% of clinical laboratories in the UK. Method: Consecutive samples received from primary care on patients with SCH who had a raised thyroid‐stimulating hormone (TSH) <10 mIU/L and a normal free thyroxine (fT4) from two laboratories using either Roche or Abbott thyroid assays were identified over 10 working days. Following identification, samples were analysed at the other site within 24 hours. Diagnostic and management discordance were studied using the relevant manufacturer‐provided reference ranges. Results: We identified 93 patients with SCH (53 using the Roche assay). Roche TSH and fT4 results were respectively 40% ± 15% and 16% ± 7% higher ( P  < .001) compared to Abbott results. Of the 93 patients, 41 (44%) were concordant for SCH on both methods. Of the 53 patients with SCH on the Roche assays, 40 (75.5%) had normal thyroid function and 13 (24.5%) had SCH when analysed using the Abbott assays. Of the 40 patients with SCH on the Abbott assays, 28 (70%) had SCH and 12 (30%) had results indicative for levothyroxine replacement when analysed on the Roche assays. Of these 12 patients, four had TSH > 10 mIU/L, five had low fT4 and three had both. Conclusion: The diagnosis and management of SCH is strikingly different when using TSH and fT4 assays provided by Abbott Laboratories and Roche Diagnostics. Clinicians and laboratorians should be aware that between‐assay differences and variations in reference ranges will directly impact the diagnosis and management of subclinical hypothyroidism.